Կարուց վիճակի փոխանորդ Գարեգին Եպիսկոպոս Սաթունյանի - Հակոբ Մուրադյան (Մայր Աթոռոյ Սրբոյ Էջմիածնի)
Многие главы епархий и викарии Армянской Церкви оставили воспоминания, дневники, отчеты, ведомости, представляющие собой весьма ценный и интересный материал для исследователей. К их числу относится ведомость главы Карсской епархии епископа Гарегина Сатуняна, хранящаяся в архиве «Разных авторов» Института древних рукописей Матенадаран им. Маштоца. В ней приводится краткое описание церквей, монастырей, школ, быта, традиций, а представляется перечень населения указанной епархии. Ведомость содержит достоверные сведения и может служить первоисточником. Many Primates of dioceses and Vicars of the Armenian Church left memories, diaries, reports, statements, which are very valuable and interesting material for researchers. They also include the bulletin of Bishop Karekin Satunyan, Vicar of Kars Diocese, which is stored in the archive called «Various authors» of Matenadaran named after Mashtots, Institute of Ancient Manuscripts. It briefly describes the situation of churches and monasteries entrusted to him, schools, population, lifestyle and customs, which is a valuable and significant source of information.
Keywords: Christianity; History of the Armenian Church